PENDAMPINGAN DIGITAL MARKETING: TIPS BERJUALAN DAN BERIKLAN MELALUI INSTAADS - Dida Nurhaida; Shafrani Dizar; Irma Ade Alisa; Ai Kartini; Syalendra Malik Suteja; Thazqia Dhia Hasna (Universitas Trisakti, 2022)
The purpose of this community development activity is to equip partner with skills in utilizing social media accounts Instagram as a tool for promotion and online sales of potato chip products produced by the partner by online through direct mentoring. The material provided starts from an introduction to the features on Instargam and their functions, and then tutorials in creating interesting content and photos to increase promotions, as well as tips and tricks on how to post and advertise on Instagram. From the results of the mentoring activities, it can be seen that partners are able to make marketing plans and utilize Instagram social media independently. Partners have started to actively update and post regularly with interesting content and captions. The activity ends with the evaluation of effectiveness activity by monitoring the development of the skills and her business for three months.